Significance of the “Coefficient of Structural Development” from a Viewpoint of Soil Physical Properties and Methods to improve Soil Structure: Studies on the relation between physical and engineering Properties and soil structure of clayey soils (III) - YAZAWA, Masao; MAEDA, Takashi (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1984)
The authors proposed the “Coefficient of structural development (Csd) ” as the index to evaluate numerically the structural development of clayey soils in the previous papers. In this paper, the significance of Csd from a viewpoint of soil physical properties was investigated for thiry-five clayey soils in which eighteen were nonvolcanic ash soils and seventeen volcanic ash soils. The relations between the soil structural development and factors such as clay content, humus content etc were investigated, and the methods to improve soil structure were discussed. Results obtained are summarized as follows. 1) Csd showed positive correlations (significant at 0.01 or 0.05 level) with saturated hydraulic conductivity, water content under pF 3, gravitational water content (under pF 1.8) and available water content (pF 1.8-3).(Figs. 1-3, Table 2) 2) On the basis of desirable soil physical conditions for upland field, the following relations betweenCsd values and the degree of soil structural development were obtained: for Csd value <1. 5, ill-developed: for Csd value 1.5-1.8, normal; and for Csd value >1. 8, well-developed.(Figs. 1-4) 3) A positive proportional relation between Csd value and structural pore volume was recognized.(Fig. 5) 4) Clay content showed a negative correlation with structural pore volume, and especially, the structure of nonvolcanic ash soils with clay contens above 40% was ill-developed.(Fig. 6) 5) Humus contens showed a positive correlation with structural pore volume, and the humus content required to contribute positively to structural development was above 7%.(Fig. 7) 6) Saturation degree at pF 1.8 showed a negative correlation with structural pore volume, this means that the drying-wetting process is important for the structural development.(Table 3) 7) Two kinds of soils with ill-developed structure were recognized, and drainage improvement, subsoil improvement, soil softening, addition of organic materials (compost and green manure). and so on were discussed as the methods for improving the soil structure.(Table 4 and 5)